Graft Copolymers of Carboxymethyl Cellulose and Poly(N-vinylimidazole) as Promising Carriers for Metronidazole - Maria S. Lavlinskaya; Anastasia A. Mikhaylova; Egor I. Kuznetsov; Ivan A. Zhuravlev; Nikita A. Balbekov; Igor A. Saranov; Andrey V. Sorokin (Polysaccharides, 2024)
Carboxymethyl cellulose sodium salt is a common water-soluble derivative of cellulose. It serves as a bioinert mucoadhesive material extensively used in biomedicine, particularly for crafting targeted drug delivery systems. In our study, we demonstrate that graft copolymers of sodium carboxymethyl-cellulose with poly(N-vinylimidazole) can function as carriers for the antibacterial drug metronidazole. Non-covalent associations form between the components, excluding the involvement of the nitro groups of the drug in the interaction. These loaded copolymers exhibit the capability to release the drug under conditions mimicking the stomach environment for up to 48 h. This renders the obtained associations promising candidates for the development of a metronidazole-targeted delivery system.